Penerapan Konsep 5S (Seiri, Seiton,Seiso, Seiketsu, Shitsuke) di Kid Corner PUSTAKA - Juznia Andriani (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2019)
The concept of 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) originating from Japan has been widely used in the industrial world with the aim of keeping the work environment orderly, reducing waste and comfortable for work atmosphere. This paper aims to examine the application of 5S in kid corner REFERENCES with respect to the aspect of room condition, human resources and management. The study began September 2017 until February 2018. Data collection was done through interviews with the managers of office boy and Head of Household Equipment and users are 6 students of Monttesory and one teacher as a sample. On-the-ground observations were made to see the application of the 5S concept: the cycle methodology: summarize, straighten, clean, standardize and maintain or discipline the cycle. To measure the comfort level used questionnaire. The resultsof the study show that from the aspect of the condition of the room lighting, humidity and temperature has been comfortable for users. In terms of security, alarms, CCTV, fire extinguishers and PPPK boxes are available. But there is still a shortage for people with disabilities because the road to go to the location kid corner is still steep. For the blind there is still no shortage of Braille collection. Human resources involved in the implementation of 5S has performed its duties well, office boy has been working according to the procedure, Head of Householdand Equipment and leadership of PUSTAKA has done its job by routinely monitoring the management of kid corner activities. In terms of management concept 5S always socialized in every opportunity meeting or meeting equipped with SOP management. Implementation of 5S has succeeded in reducing waste and tidying up the location of the kid corner so that the goods are arranged in place so that the librarian and the librarian feel comfortable in the activity.